2020
DOI: 10.21203/rs.3.rs-16804/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective effects of DPP-4 inhibitor on podocyte injury in glomerular diseases

Abstract: Background Dipeptidyl peptidase-4 (DPP-4) is a serine protease that inhibits the degradation of glucagon-like peptide 1. DPP-4 inhibitors are used worldwide to treat type 2 diabetes mellitus and were recently shown to have pleiotropic effects such as anti-oxidant, anti-inflammatory, and anti-fibrotic actions. DPP-4 inhibitors improve albuminuria and renal injury including glomerular damage independent of its hypoglycemic effect. Although DPP-4 is mainly expressed in the kidney, the physiological function of D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…DPP-4 inhibitors can increase the level of GLP-1 and GLP-2 by inhibiting DPP-4 (Ning et al, 2020;Yan et al, 2016). Studies have confirmed that DPP-4 inhibitors exhibit renoprotective effects via inhibiting inflammation and oxidative stress, preventing podocyte injury, and delaying glomerulosclerosis in DKD (Kawanami et al, 2021;Kubo et al, 2020;Mima, 2022). Sitagliptin, a DPP-4 inhibitor, was reported to regulate the dysbiosis of gut microbiota in a rat model of diabetes, and the potential beneficial effect may be related to GLP-2 (Yan et al, 2016).…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…DPP-4 inhibitors can increase the level of GLP-1 and GLP-2 by inhibiting DPP-4 (Ning et al, 2020;Yan et al, 2016). Studies have confirmed that DPP-4 inhibitors exhibit renoprotective effects via inhibiting inflammation and oxidative stress, preventing podocyte injury, and delaying glomerulosclerosis in DKD (Kawanami et al, 2021;Kubo et al, 2020;Mima, 2022). Sitagliptin, a DPP-4 inhibitor, was reported to regulate the dysbiosis of gut microbiota in a rat model of diabetes, and the potential beneficial effect may be related to GLP-2 (Yan et al, 2016).…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%